Geography of a sports metropolis - Gabriel M. Ahlfeldt; Arne Feddersen (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2008)
This study analyses the sports infrastructure of Hamburg, Germany, from the residents' perspective. Empirical evidence is provided for the Sports Place Theory developed by BALE (2003) using a micro-level dataset of 1,319 sports facilities, which is merged with highly disaggregated data on population, socio-demographic characteristics and land values. In line with the theory, small and medium facilities on average are found to have catchment areas ranging from 1,000 to 2,500m. Similarly, large facilities carry out services within an area of up to 5,000m. Based on implicit travel costs, locations' endowment of sports infrastructure is captured by potentiality variables, while accounting for natural and unnatural barriers. Given potential demand, central areas are found to be relatively underprovided with a sports infrastructure compared to peripheral areas where opportunity cost in the form of price of land is lower. The determinants of spatial distribution vary systematically across types of sports facilities. Publicly provided open sports fields and sport halls tend to be concentrated in areas of relatively low income which is in line with their social infrastructure character, emphasized by local authorities. In contrast, there is a clear tendency for market allocated tennis facilities to follow purchasing power. Areas with higher proportions of foreigners are subject to relatively lower provision of a sports infrastructure, which contradicts the stated ambitions of planning authorities. To meet the implicit call for action, detailed maps of relative supply indicating privileged and disadvantaged areas offer useful guidance.
Keywords: H4; R53; 330; Sports Facilities; Sports Geography; Public Infrastructure